HIFU-CCL19/21 Axis Enhances Dendritic Cell Vaccine Efficacy in the Tumor Microenvironment - Bum-Seo Baek; Hyunmi Park; Ji-Woong Choi; Eun-Young Lee; Seung-Yong Seong (Pharmaceutics)
Background/Objectives: Effectively targeting treatment-resistant tumor cells, particularly cancer stem cells (CSCs) involved in tumor recurrence, remains a major challenge in immunotherapy. This study examines the potential of combining mechanical high-intensity focused ultrasound (M-HIFU) with dendritic cell (DC) vaccines to enhance immune responses against OLFM4-expressing tumors, a CSC marker linked to immune evasion and tumor growth. Methods: M-HIFU was applied to induce immunogenic cell death by mechanically disrupting tumor cells, releasing tumor-associated antigens and creating an immunostimulatory environment. DC vaccines loaded with OLFM4 were then administered to boost the immune response within this primed environment. Results: The combination of M-HIFU and DC vaccine significantly inhibited tumor growth and metastasis, with enhanced T-cell activation and increased recruitment of immune cells due to elevated chemokines CCL19 and CCL21. This synergy promoted immune memory, reducing the likelihood of recurrence. Conclusions: M-HIFU effectively promotes the migration of DC vaccines through CCL19/21, presenting a promising approach for cancer treatment. Further studies are recommended to optimize this combination for clinical applications, with potential to improve patient outcomes in challenging cancer types.